(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Malignant tumors of the gastrointestinal (GI) tract remain one of the leading causes of cancer morbidity and mortality worldwide. Late diagnosis persists as a major challenge, with over 60% of patients being identified at stages III–IV. Endoscopic monitoring utilizing advanced mucosal visualization technologies significantly improves early detection of neoplastic lesions and precancerous conditions. The use of HD-endoscopy, narrow-band imaging (NBI), endoscopic ultrasonography, capsule endoscopy, and artificial intelligence-assisted systems has demonstrated a 25–40% reduction in mortality according to international data. The article presents an overview of current endoscopic approaches and their impact on improving oncological outcomes.